Effect of crystallization on the electronic and optical properties of archetypical porphyrins - Malcioglu, Osman; Bechis, Irene; Bockstedte, Michel Georg (Physical Chemistry Chemical Physics, 2020)
Thin porphyrin films as employed in modern optical devices or photovoltaic applications show deviating electronic and optical properties from the gasphase species. Any understanding of the physical origin may pave way to a specific engineering of these properties via ligand or substituent control. Here we investigate the impact of crystallization of prototypical porphyrins on the electronic levels and optical properties in the framework of density functional theory and many-body perturbation theory. Crystallization substantially shrinks the HOMO-LUMO gap based on polarization effects. We find a shift of the HOMO to higher energy is consistent with recent experiment of MgTPP multilayer film on Ag (100) [A. Classen et al., Phys. Rev. B, 2017, 95, 115414]. Calculated excitation spectra demonstrate a significant redshift of excitation bands except for the Q bands. These lowest excitation bands, in stark contrast to the strong HOMO-LUMO gap renormalization, remain essentially the same as in the gas phase. Our work underlines the possibility of band-gap engineering via ligand-controlled modification of the polarizability.
CRIS-Team WoS Importer:2020-03-27

Electroluminescence: From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins (Adv. Funct. Mater. 37/2016) - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Martí, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel Georg; Costa, Ruben Dario (Advanced Functional Materials, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Electronic structure of tetraphenylporphyrin layers on Ag(100) - Classen, Andrej; Pöschel, Rebecca; di Filippo, Gianluca; Fauster, Thomas; Malcioglu, Osman; Bockstedte, Michel Georg (Physical Review B, 2017)

From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Marti, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel; Costa, Ruben D. (Advanced Functional Materials, 2016)
The differences in the electroluminescence (EL) of red-emitting free-base (H2TPP) and Zn-metalated (ZnTPP) archetypal porphyrins are rationalized in light-emitting electrochemical cells by means of an electric-field dependent effect, leading to whitish and reddish devices, respectively. Although H2TPP shows superior electrochemical and photophysical features compared to ZnTPP, devices prepared with ZnTPP surprisingly stand out with a deep-red EL similar to its photoluminescence (PL), while H2TPP devices feature unexpected whitish EL. Standard arguments such as degradation, device architecture, device mechanism, and changes in the nature of the emitting excited states are discarded. Based on electrochemical impedance spectroscopy and first-principles electronic structure methods, we provide evidence that the EL originates from two H2TPP regioisomers, in which the inner ring H atoms are placed in collinear and vicinal configurations. The combination of their optical features provides an explanation for both the high- and low-energy EL features. Here, the emitting excited state nature is ascribed to the Q bands, since the Soret excited states remain high in energy. This contrasts to what is traditionally postulated in reports focused on H2TPP lighting devices. Hence, this work provides a new explanation for the nature of the high-energy EL band of H2TPP that might inspire future works focused on white-emitting molecular-based devices.
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources